An Examination Of Ethiopia’s Anti -Terrorism Proclamation On Fundamental Human Rights - Sekyere, Peter; Asare, Bossman (European Scientific Journal, ESJ, 2016)
Since the enactment of Ethiopia’s Proclamation on Anti-Terrorism in August 2009, at least11 journalists have been convicted, each sentenced to at least 10 years imprisonment. There are concerns that the proclamation limits the right to freedom of thought, opinion and expression, provided for in Ethiopia’s Constitution. Through the lens of the right to freedom of thought, opinion and expression, the paper argues that Ethiopia’s Anti-Terrorism Proclamation violates the human rights of people within its jurisdiction. It finds that there is a real potential for the state to crack down on political dissent in governance and curtail the growth of democracy in Ethiopia.